Postpartum depressive disorders in different modes of delivery in Hospital Tengku Ampuan Afzan - Win,Nilar (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Postpartum Depression (PPD) imposes significant public health burden around the world. Researchers had tried to find many methods to screen and diagnose PPD as well as its predictors. The aim of this study is to examine the associations between postpartum depressive disorders and modes of delivery, socio-demographic and obstetric risk factors. This prospective cohort study was conducted in Postpartum ward of Hospital Tengku Ampuan Afzan from November 2017 until June 2018. Women who were aged more than 18 years and can communicate in Bahasa Melayu or English were recruited as study population. Among 457 participants, 185 women had normal vaginal delivery, 109 had instrumental delivery and 163 had Caesarean delivery. Antenatal and socio-demographic background were recorded, then social support was assessed using Multidimensional Scale of Perceived Social Support (MSPSS). Participants were interviewed using Edinburg Postpartum Depression Scale within 48 hours, 2 weeks and 6 weeks after delivery. Second and third interview were conducted via telephone. A cut-off point of ≥ 12 on EPDS was used as a measure of the primary outcome, depression. There were no association between depressive symptoms at 2 weeks postpartum and delivery modes (chi square test 6.384, p value 0.172). Elective Caesarean delivery has lower risk of developing PPD (crude OR 0.310, 95 % CI 0.131-0.375, p < 0.05). Normal vaginal delivery, instrumental delivery and emergency Caesarean delivery were not found to be associated with PPD. The simple regression identified 4 predictors for PPD: older maternal age (crude OR 0.138, 95 % CI 0.074 - 0.258), prolonged labour duration (crude OR 1.089, 95 % CI 1.008 - 1.177), primiparous women (crude OR 0.156, 95 % CI 0.66 - 0.369) and low income (crude OR 4.262, 95 % CI 1.418 - 12.806). However, age is the most significant factor when other confounders were adjusted (adjusted OR 0.112, 95 % CI 0.55 - 0.231). In conclusion, mode of delivery was associated with PPD but did not factor into the main effect model.